Analysis of Nurse Characteristics with Work Motivation in Wamena Hospital - Lamere, Moses; Wardani, Ratna (Journal for Quality in Public Health, 2021)
Lately there has been attention to work dissatisfaction and declining quality. Most people find it difficult to motivate themselves, therefore it is not surprising that motivating others is a difficult and complicated task. Motivation indicates the process of movement, including the encouraging situation that arises within the individual, the behavior caused by the situation and the purpose or end of the movement or action. The purpose of this study was to analyze the relationship of nurse characteristics with work motivation in Wamena Hospital inpatient room. This type of research is quantitative with an observational approach. The population is the entire nursing plant in Wamena Hospital with 186 people. Large samples were taken as many as 64 respondents. Sampling techniques used in this study is a simple random sampling technique. Based on the results of the study it is known that there is a meaningful relationship between age, working period and position with work motivation. While there are several factors that are not related to work motivation, namely gender, education and marital status. The statistical test used is path analysis. Statistical tests can be concluded that there is a meaningful relationship to variables as follows: the characteristics of nurses that affect work motivation are age, years of service and position, while the characteristics of gender, education and marital status do not have a significant relationship with work motivation. Based on the results of the study is expected to improve the ability and insight of nursing and motivation of work so that their productivity does not decrease. For example, give remuneration, promotion and periodic reward for outstanding nurses will encourage the motivation of nurse work to develop.